2020
DOI: 10.5219/1374
|View full text |Cite
|
Sign up to set email alerts
|

Fruit red colorants impact on the antiradical activity determined by DPPH method

Abstract: This work is focused on the determination of antiradical activity (ARA) by the method of free radical scavenging of 2,2-Diphenyl-1-picrylhydrazyl (DPPH). Since the DPPH solution is intense purple-coloured and absorbs at a wavelength of 517 nm, similar to the anthocyanin colorants of fruits, the modification of the method examined the effect of the colour of the sample extracts on the result of the ARA determination. Statistical evaluation of the results of the analyses using Youden's graphing method revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The reduction reaction of the DPPH radical took place when it received hydrogen from the antioxidant(s), resulting in the formation of DPPH-H (non-radical) and changed its color from purple to yellow. 17,19,56 Based on the EC 50 values, the DPPH scavenging activity shown by LAA was higher than TQ because TQ has a lower capacity of work as antioxidant hydrogen or electron donors. 52 LAA is reported to scavenge DPPH radicals in MeOH by a hydrogen transfer reaction to form DPPH-H. 18 Some studies reported that the EC 50 value of LAA was around 20 mM for the DPPH assay.…”
Section: Resultsmentioning
confidence: 99%
“…The reduction reaction of the DPPH radical took place when it received hydrogen from the antioxidant(s), resulting in the formation of DPPH-H (non-radical) and changed its color from purple to yellow. 17,19,56 Based on the EC 50 values, the DPPH scavenging activity shown by LAA was higher than TQ because TQ has a lower capacity of work as antioxidant hydrogen or electron donors. 52 LAA is reported to scavenge DPPH radicals in MeOH by a hydrogen transfer reaction to form DPPH-H. 18 Some studies reported that the EC 50 value of LAA was around 20 mM for the DPPH assay.…”
Section: Resultsmentioning
confidence: 99%